Anti-Severe Acute Respiratory Syndrome Coronavirus 2 Hyperimmune Immunoglobulin Demonstrates Potent Neutralization and Antibody-Dependent Cellular Cytotoxicity and Phagocytosis Through N and S Proteins. (25th October 2021) - Díez, José María; Romero, Carolina; Cruz, María; Vandeberg, Peter; Merritt, William Keither; Pradenas, Edwards; Trinité, Benjamin; Blanco, Julià; Clotet, Bonaventura; Willis, Todd; Gajardo, Rodrigo
Abstract: Background: Although coronavirus disease 2019 (COVID-19) vaccinations have provided a significant reduction in infections, effective COVID-19 treatments remain an urgent need. Methods: Functional characterization of anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) hyperimmune immunoglobulin (hIG) from human convalescent plasma was performed by different virus neutralization methodologies (plaque reduction, virus-induced cytotoxicity, median tissue culture infectious dose [TCID50 ] reduction, and immunofluorimetry) at different laboratories using geographically different SARS-CoV-2 isolates (USA [1], Italy [1], and Spain [2]; 2 containing the D614G mutation). Neutralization capacity against the original Wuhan SARS-CoV-2 strain and variants (D614G mutant, B.1.1.7, P.1, and B.1.351) was evaluated using a pseudovirus expressing the corresponding spike (S) protein. Antibody-dependent cellular cytotoxicity (ADCC) and antibody-dependent cellular phagocytosis (ADCP) was also evaluated. Results: All SARS-CoV-2 isolates were potently neutralized by hIG as shown by all 4 methodologies. Wild-type SARS-CoV-2 and variants were effectively neutralized using the pseudovirus. The hIG (IgG type) induced ADCC and ADCP against SARS-CoV-2 N and S proteins but not E protein. Very low concentrations (25–100 µg IgG/mL) were required. A potent effect was triggered by antibodies in hIG solutions against the SARS-CoV-2 S and N proteins. Conclusions: Beyond neutralization, IgG Fc-dependent pathways may play a role in combatting SARS-CoV-2 infections using COVID-19 hIG. This could be especially relevant for the treatment of more neutralization-resistant SARS-CoV-2 variants. Abstract : Anti-SARS-CoV-2 hyperimmune globulin potently neutralized viral isolates and S-protein-expressing pseudoviruses representing wild-type virus and viral variants. This hyperimmune globulin also induced antibody-dependent cellular toxicity and phagocytosis via antibodies to the N and S proteins.